Integration of the Value of Kemalikussalehan in Chemistry Learning through Teaching Modules Based on Culturally Responsive Teaching (CRT) and Technological Pedagogical Content Knowledge (TPACK) - Lisa Aufiya; Putri Kirani; Dea Kumala Dewi; Sri Setiawaty (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to describe the implementation of an integrated teaching module on the value of Kemalikussalehan based on Culturally Responsive Teaching (CRT) and Technological Pedagogical Content Knowledge (TPACK) on the material of buffer solutions at SMA Negeri 5 Lhokseumawe. This approach is motivated by the need for chemistry learning that emphasizes cognitive aspects and builds students' character and identity through the integration of local values and technology. The type of research used is Educational Design Research (EDR) with the Plomp Development model. The research was conducted until the lecturer's validity test. Validity using Aiken's V formula produced 0.90 with a valid category. The study results showed that implementing this teaching module increased students' motivation, active involvement, and conceptual understanding of the material of buffer solutions. In addition, students showed an attitude of tolerance, cooperation, and concern for the environment as a reflection of religious values integrated into learning.